Synthesis of Kojic Ester Derivatives as Potential Antibacterial Agent - Carolynne Zie Wei Sie; Zainab Ngaini; Nurashikin Suhaili; Eswaran Madiahlagan (Journal of Chemistry)
The search for lead product with beneficial pharmacological properties has become a great challenge and costly. Extraction and synthetic modification of bioactive compounds from natural resources has gained great attention and is cost effective. In this study, kojic acid was produced from fungal fermentation, using sago waste as substrate, and chemically incorporated with chalcones and azobenzene to form a series of kojic ester derivatives and evaluated for antibacterial activities. Kojic ester bearing halogenated chalcone demonstrated active inhibition against Staphylococcus aureus compared to that of standard ampicillin. The inhibition increased as the electronegativity of halogens decreased, while incorporation of azobenzene derivatives on kojic acid backbone demonstrated fair antibacterial activity against Escherichia coli with minimum inhibitory concentration (MIC) of 190–330 ppm. The presence of C=C and N=N reactive moieties in both chalcone and azo molecules contributed to the potential biological activities of the kojic acid ester.